2012
DOI: 10.1002/jcc.23011
|View full text |Cite
|
Sign up to set email alerts
|

Density functional theory study of high‐pressure effect on crystalline 4,4′,6,6′‐tetra(azido)hydrazo‐1,3,5‐triazine

Abstract: Periodic density functional theory calculations are performed to study the hydrostatic compression effects on the structure, electronic, and thermodynamic properties of the energetic polyazide 4,4',6,6'-tetra(azido)hydrazo-1,3,5-triazine (TAHT) in the range of 0-100 GPa. At the ambient pressure, the local density approximation/Ceperley-Alder exchange-correlation potential parameterized by Perdew and Zunger relaxed crystal structure compares well with the experimental results. The predicted heat of sublimation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 64 publications
2
5
0
Order By: Relevance
“…The electronic structures, detonation properties, and pyrolysis mechanism of TAHT and its hypothesized derivatives have been investigated using density functional theory (DFT, B3LYP) . It has been found that TAHT has better thermal stability than its analogue TAAT, which is in agreement with the experiments. Further theoretical investigations have been carried out for both TAHT and TAAT in terms of their geometric and electronic parameters by considering the effect of the crystalline field. , TAHT has a theoretical heat of sublimation of 38.68 kcal mol –1 , while its detonation velocity and detonation pressure in the solid state are predicted to be 7.44 km s –1 and 23.71 GPa, respectively. An analysis of the electronic structure reveals that the impact sensitivity of TAHT and TAAT could be increased under pressure.…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…The electronic structures, detonation properties, and pyrolysis mechanism of TAHT and its hypothesized derivatives have been investigated using density functional theory (DFT, B3LYP) . It has been found that TAHT has better thermal stability than its analogue TAAT, which is in agreement with the experiments. Further theoretical investigations have been carried out for both TAHT and TAAT in terms of their geometric and electronic parameters by considering the effect of the crystalline field. , TAHT has a theoretical heat of sublimation of 38.68 kcal mol –1 , while its detonation velocity and detonation pressure in the solid state are predicted to be 7.44 km s –1 and 23.71 GPa, respectively. An analysis of the electronic structure reveals that the impact sensitivity of TAHT and TAAT could be increased under pressure.…”
Section: Introductionsupporting
confidence: 74%
“…It has been found that TAHT has better thermal stability than its analogue TAAT, which is in agreement with the experiments [19][20][21] . Further theoretical investigations have been carried out for both TAHT and TAAT in terms of their geometric and electronic parameters by considering the effect of the crystalline field 22,23 . TAHT has theoretical heat of sublimation of 38.68 kcal mol -1 , while its detonation velocity and detonation pressure in solid state are predicted to be 7.44 km s -1 and 23.71 GPa,…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that TAHT has better thermal stability than its analogue TAAT, which is in agreement with the experimental results [26,27]. Further theoretical investigations have been carried out for both TAHT and TAAT in terms of their geometric and electronic parameters by considering the effect of the crystalline field [28,29]. Another compound which contains 4,6-diazido-1,3,5-triazineyl group is 4,6-diazido-N-(2,4,6-trinitrophenyl)-1,3,5-triazin-2-amine (TANDAzT).…”
Section: Introductionsupporting
confidence: 67%
“…In the past decades, our group has done lots of studies about high energetic materials on various properties . Among them, a nitro cage compound, namely 4‐trinitroethyl‐2, 6, 8, 10, 12‐pentanitrohexaazaisowurtzitane (TNE‐CL‐20) (in Figure ) prepared in recent years (in Figure ), was researched on its structural and energetic properties in gas phase .…”
Section: Introductionmentioning
confidence: 99%